Alveolar Proteinosis Secondary to M. tuberculosis, in a Patient with Transient CD4 Lymphocytopenia Due to Cryptococcus neoformans Infection: First Case in the Literature - Daniel Augusto Martin Arsanios; Diego Alejandro Cubides-Díaz; Natalia Muñoz-Angulo; Maria Alejandra Perez-Hernandez; Marlyn Zamora Posada; Mónica Briceño Torres; Carlos Mauricio Calderón Vargas (MDPI AG, 2022)
Transient CD4 lymphocytopenia is defined as the transitory presence of CD4+ T lymphocyte fewer than 300 cells/mm3 or less than 20% of T cells without HIV infection. It can occur due to multiple causes; however, it is rare for it to occur due to opportunistic infections. Few cases have been described in the literature where antimicrobial treatment normalizes the CD4 count, being more frequent in Mycobacterium tuberculosis infections. To date, this phenomenon has not been described in Cryptococcus neoformans infections. This would be the first reported case according to our knowledge, of a patient who normalizes CD4 count after antifungal treatment, later developing alveolar proteinosis due to M. Tuberculosis.